Pengaruh Kepuasan terhadap Loyalitas Konsumen Member di Mini Soccer Bumara di Kota Palembang - Muamar Muamar; Muti Fajar; Endie Riyoko (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to find information about whether members are satisfied with the service provided at the Bumara mini soccer field in the city of Palembang, South Sumatra. In this research, the method used is correlational. In this study, the population was 76 Mini Soccer Bumara members. Before carrying out the analysis test, a number of requirements tests were first carried out to determine the suitability of the X and Y data. The requirements test included several test stages using the following formula: f test, validity test, test simple linear regression. Based on data analysis from research on the influence of Mini Soccer Bumara member satisfaction, there is a significant relationship, namely showing an fcount value of 319.663 with a significance level of 0.001. The significance value is smaller than 0.05. Thus fcount> ftable (319.663>3.12) which means that the hypothesis in this research has a positive effect on customer loyalty.